Financial planning, access to capital and financial performance of licensed chemical shops in the Kumasi metropolis, Ghana - Quainoo, Elizabeth (University of Cape Coast, 2024)
Financial performance helps small businesses to operate efficiently, generate effective income, survive, and expand by observing environmental opportunities and threats. Financial planning and access to capital are important factors for business financial performance. This study examined the effect of financial planning, access to capital and financial performance of Licensed Chemical Shops (LCSs) in the Kumasi Metropolis of Ghana. Drawing on contingency, pecking order and resource-based view theories, the study hypothesized that financial planning has a significant effect on financial performance as well as access to capital. Also, the study hypothesized that financial planning has a significant effect on access to capital, in such a way that the latter significantly mediates the relationship between financial planning and financial performance. Data were collected, using a structured questionnaire distributed to 257 LCSs and responded by the owners or their shop attendants in the absence of the owners. The study employed a simple random sampling technique with the use of SPSS version 27 for coding and running of the study descriptives. SMART PLS 4 was used for data processing of the hypotheses. The findings indicated that: (1) financial planning significantly and positively affects financial performance; (2) access to capital significantly affect financial performance with a weaker positive effect; (3) financial planning significantly and positively affects access to capital; and (4) access to capital partially mediates the relationship between financial planning and financial performance. The study recommended that LCSs prioritize comprehensive financial planning strategies to enhance their financial health and performance.
x,127p:,ill
Keywords: Access to capital Financial performance Financial planning Licensed Chemical Shops (LCSs)